Nomenclatura y diagnóstico de la amiloidosis desde una perspectiva histórica - Aguirre, Maria Adela (2021)
Introducción: Amyloidosis is a rare chronic disease, characterized by extracellular deposition of fibrillar proteins in various organs and tissues. The clinical manifestations are based on the site of the deposits and the precursor protein involved. The main diagnostic tool is clinical suspicion. The prognosis is usually bleak. The objective of this study is to describe the events that happened over time to reach what we know today as amyloidosis.Materials and methods: an exploratory, narrative, historical study was carried out. Primary sources and affected documentary sources were reviewed. Development: The first descriptions of patients with amyloidosis date from the mid 1600 AD. These were anatomical descriptions, reported from autopsies of patients. The first approximations to the diagnosis were through stains with iodine and anilines, finally reaching X-ray diffraction, and microscopy with polarized light under staining with Congo red.Conclusions: Despite being a nosological entity known for four centuries, the difficulties to characterize the origin and understand the pathophysiology of amyloidosis still remain. For decades there were controversies about the nomenclature and the nature of amyloid material. The diagnosis and management of this disease follow the control of advances in technology, currently being a challenge in the management of patients suffering from amyloidosis.Keywords: amiloidose; history; amilóide.